Um estudo sobre as políticas editoriais da editora da Universidade Estadual de Londrina (EDUEL) e da Universidade Estadual de Maringá (EDUEM) - Harfuch, Carlos Alberto Cury (2014)
The role of a public university press in Brazil surpasses the boundaries of the field and reaches dimensions that require the formation of an effective policy to enable it to fully develop its autonomy. Thus, this research proposes to investigate the modus operandi of two university presses from Paraná, EDUEL(Londrina State University Press) and EDUEM (Maringá State University Press)in order to capture more acutely the challenges that the public university press faces to consolidate itself in publishing and conquer their autonomy. To thise nd, we chose to perform interviews with current directors and former directors of both publishers, and Leilah Bufrem Santiago, in order to identify not only the difficulties but also the progress made in this direction. As a theoretical basis for this field research, it becomes a priori the Field Theory of Bourdieu and analysis of the activity and performance of public publisher in Paraná constant in the work of Leilah Santiago Bufrem. Methodologically, the research is divided into three chapters, which guiding thread starts in the theory of these two thinkers, follows with the apparatus of the material provided by both public institutions concerned (sites and statutes), and culminates in the analysis of the interviews themselves. Finally, the survey of the relevant issues raised by those interviewed allows the offer of suggestions for the formulation of public policies for the sector.